Influence of Neutron Sources and 10B Concentration on Boron Neutron Capture Therapy for Shallow and Deeper Non-small Cell Lung Cancer. Issue 3 (March 2017) - Yu, Haiyan; Tang, Xiaobin; Shu, Diyun; Liu, Yuanhao; Geng, Changran; Gong, Chunhui; Hang, Shuang; Chen, Da
Abstract : Abstract: Boron Neutron Capture Therapy (BNCT) is a radiotherapy that combines biological targeting and high Linear Energy Transfer (LET). It is considered a potential therapeutic approach for non-small cell lung cancer (NSCLC). It could avoid the inaccurate treatment caused by the lung motion during radiotherapy, because the dose deposition mainly depends on the boron localization and neutron source. Thus, 10 B concentration and neutron sources are both principal factors of BNCT, and they play significant roles in the curative effect of BNCT for different cases. The purpose was to explore the feasibility of BNCT treatment for NSCLC with either of two neutron sources (the epithermal reactor at the Massachusetts Institute of Technology named "MIT source" and the accelerator neutron source designed in Argentina named "MEC source") and various boron concentrations. Shallow and deeper lung tumors were defined in the Chinese hybrid radiation phantom, and the Monte Carlo method was used to calculate the dose to tumors and healthy organs. The MEC source was more appropriate to treat the shallow tumor (depth of 6 cm) with a shorter treatment time. However, the MIT source was more suitable for deep lung tumor (depth of 9 cm) treatment, as the MEC source is more likely to exceed the skin dose limit. Thus, a neutron source consisting of more fast neutrons is not necessarily suitable for deep treatment of lung tumors. Theoretical distribution of 10 B in tumors and organs at risk (especially skin) was obtained to meet the treatable requirement of BNCT, which may provide the references to identify the feasibility of BNCT for the treatment of lung cancer using these two neutron sources in future clinical applications.